2020
DOI: 10.1093/qjmed/hcaa052.024
|View full text |Cite
|
Sign up to set email alerts
|

The study of Mean Platelet Volume (MPV) as a Potential Risk Factor for Macrovascular Complications (Ischemic Heart Disease and Cerebrovascular Stroke) in Type 2 Diabetes Mellitus

Abstract: Background Type 2 diabetes mellitus (T2DM) has reached global epidemic proportions, with more than 382 million people affected according to 2013 estimate. By 2035, its prevalence is expected to reach 471 million, meaning that 10% of the world’s population will have diabetes. Patients with diabetes often suffer from metabolic abnormalities, poor glycemic control, oxidative stress, insulin resistance, and low-grade inflammation. These conditions trigger vascular dysfunction, which predisposes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…A meta-analysis of MPV levels in diabetic retinopathy revealed that MPV levels were significantly higher in patients with diabetic retinopathy as compared to those without diabetic retinopathy [25]. Our study found that higher values of MPV were associated with a higher prevalence of microvascular and macrovascular complications, which is similar to other studies [26,27]. But, on stratification of MPV with high HbA1c (>10), the significant association with vascular complications was lost.…”
Section: Discussionsupporting
confidence: 86%
“…A meta-analysis of MPV levels in diabetic retinopathy revealed that MPV levels were significantly higher in patients with diabetic retinopathy as compared to those without diabetic retinopathy [25]. Our study found that higher values of MPV were associated with a higher prevalence of microvascular and macrovascular complications, which is similar to other studies [26,27]. But, on stratification of MPV with high HbA1c (>10), the significant association with vascular complications was lost.…”
Section: Discussionsupporting
confidence: 86%